Interactive Mind Map: A Medium of Language Learning in the Online Learning Era - Oktaputriviant, Nidia Rizqi; Rizqiana, Nafila Ulfa (Prosiding Seminar, 2022)
Teaching is one of prominent factors in order the Nation to achieve its national goal; educating the life of the people. The development of teaching should be integrated with the technology enhancement leading the way to expand chances to learn, freedom of learning with or from others, taking place anywhere and anytime. With this advancement of education, it now takes the role in the society 5.0 era by applying the industrial revolution 4.0 innovation like digitalized information, unlimited knowledge access, and most importantly, the online learning. Online learning is a sophistication of learning models that requires the learners to be independent, connects thousands of learners from different backgrounds, is possible to happen anywhere and anytime, and uses various resources. As online learning generally gives learners autonomy, they would have to manage themselves for achieving their learning goal. For example, using interactive media like an interactive mind map helps leaners visualize, summarize, and remember the concepts, as well as managing important information for use. MIRO is an application to create a mind map digitally. In addition, it can be used to build frameworks and diagrams collaboratively within users. Thus, making mind map through MIRO in language learning can be useful and fun because of its interactive features.